Analysis of Pharmacists Duties And Functions in The Implementation of Good Cosmetics Manufacturing Practices in The Cosmetics Industry: A 4m + 1e Fishbone Analysis - Ni Made Widi Astuti; Natalie Christanti Sukandar; Grasia Laura Boru Sihombing; Ni Nyoman Ayu Budhi Erlangga Santhi (Universitas Duta Bangsa Surakarta, 2026)
Backgorund: The implementation of Good Manufacturing Practices (GMP), or Good Cosmetic Manufacturing Practices (CPKB), is essential to ensure the quality, safety, and consistency of cosmetic products. Pharmacists play a crucial role in quality assurance, validation, documentation, and production process control. Objective: This study aimed to evaluate the contribution of pharmacists' roles and responsibilities to the implementation of GMP/CPKB and to identify the causes of nonconformities using a fishbone diagram based on the 4M + 1E approach. Method: A descriptive mixed-methods design was employed through in-depth interviews and a Likert-scale questionnaire (1–5) administered to three responsible pharmacists from PT ABC, PT DEF, and PT XYZ. The research instrument consisted of 10 assessment items covering the aspects of man, method, material, machine, and environment. The level of GMP/CPKB implementation was calculated by comparing the actual score with the maximum possible score and expressing the result as a percentage. Results: The results showed that the average GMP/CPKB implementation scores were 4.96 (99.2%) for PT ABC, 4.92 (98.4%) for PT DEF, and 4.88 (97.6%) for PT XYZ, out of a maximum score of 5. All companies were classified in the good category (81-100%). However, several nonconformities were still identified in the areas of human resources, work methods, raw materials, equipment, and the production environment. Fishbone analysis revealed that the main contributing factors included inconsistent personnel discipline, delays in updating Standard Operating Procedures (SOPs), variations in raw material quality, limitations in equipment facilities, and suboptimal environmental control. Conclusion: This study highlights the importance of pharmacists' contributions in supporting GMP/CPKB implementation through quality system supervision and control. Nevertheless, the findings remain descriptive in nature due to the limited number of respondents, consisting of only three participants.